A Matter of Scale: Historical and Environmental Factors Structure Anuran Assemblages from the Upper Madeira River, Amazonia. (13th February 2015) - Dias‐Terceiro, Randolpho G.; Kaefer, Igor Luis; de Fraga, Rafael; de Araújo, Maria Carmozina; Simões, Pedro Ivo; Lima, Albertina P.
Abstract Biogeographical history and current ecological interactions have usually been addressed separately to explain the spatial distribution of patterns of biodiversity. In this study, we evaluated the integrated effects of biogeographical and environmental factors in structuring the diurnal amphibian anuran assemblages of the upper Madeira River, southwestern Amazonia. We used a sampling design involving 98 standardized units, distributed across seven locations covering both banks of the river's course in the state of Rondônia, Brazil. We conducted searches for frogs in three campaigns between February 2010 and February 2011, aiming to: (1) evaluate the effect of the Madeira River as a biogeographic barrier at the species‐assemblage level, and (2) test the influence of seven environmental variables (vegetation structure, vegetation cover, soil nutrients, soil structure, slope, elevation, and distance from the river bank) on the spatial structure of the frog assemblages, separately on each riverbank. Thirteen species of diurnal frogs were recorded, six of which were restricted to one of the river margins. Multivariate analysis of variance indicated a significant effect of the river as a barrier. Multiple regression analyses suggested that the environmental variables structuring frog assemblages differ on either side of the river. We found that both historical elements (on a regional scale) and environmental factors (at a local scale) shaped the occurrence and distribution of frog species in the study area.